2020
DOI: 10.1186/s12917-020-2260-7
|View full text |Cite
|
Sign up to set email alerts
|

Renibacterium salmoninarum and Mycobacterium spp.: two bacterial pathogens present at low levels in wild brown trout (Salmo trutta fario) populations in Austrian rivers

Abstract: Background: Renibacterium salmoninarum and Mycobacterium sp. are important bacterial pathogens of fish. R. salmoninarum is the causative agent of bacterial kidney disease, a Gram-positive bacterium mostly known for causing chronic infections in salmonid fish, while multiple species belonging to the Mycobacterium genus have been associated with mycobacteriosis in fish as well as in human. The objective of this study was to determine the prevalence of these two bacterial pathogens in populations of wild brown tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Moreover, RT-qPCR procedures are available to detect M. marinum based on this sequence [ 84 ]. It is noteworthy that these sequences are quite similar throughout the Mycobacterium genus and, therefore, these PCRs do not generally allow one to identify the bacterium at the species level [ 85 ]. Other genes have been suggested for the development of PCR primers, including the heat shock protein 65kD gene ( hsp 65 ) [ 86 ], as summarized in Table 3 .…”
Section: Diagnosticsmentioning
confidence: 99%
“…Moreover, RT-qPCR procedures are available to detect M. marinum based on this sequence [ 84 ]. It is noteworthy that these sequences are quite similar throughout the Mycobacterium genus and, therefore, these PCRs do not generally allow one to identify the bacterium at the species level [ 85 ]. Other genes have been suggested for the development of PCR primers, including the heat shock protein 65kD gene ( hsp 65 ) [ 86 ], as summarized in Table 3 .…”
Section: Diagnosticsmentioning
confidence: 99%
“…In total, 45 water samples were collected from the Kamp and 25 samples from the Wulka River. Genomic DNAs were extracted from these samples, and PCRs were performed for each sample in order to detect the presence of NTM based on three different PCR protocols by Delghandi et al [ 34 ], Talaat et al [ 37 ], and Telenti et al [ 38 ] ( Figure 1 ). Notably, the results were identical for all three PCR protocols, and Mycobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…in water samples in order to maximize our confidence in the results. Initially, a PCR assay was performed according to the protocol developed at the University of Veterinary Medicine and published by Delghandi et al in 2020 [ 34 ], using Myco 16F1 (5′-AGCTCGTAGGTGGTTTGTCG-3′) and Myco 16R1 (5′-CCACCTTCCTCCGAGTTGAC-3′) for the detection of the 16S rRNA gene [ 34 ]. The total volume of amplification was 25 µL, comprising 12.5 µL Dream Taq Green PCR Master Mix, 1 µL of each primer (10 pmol) and 4 µL eDNA solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal transmission via water is considered to be limited since R. salmoninarum is not able to survive outside the host for longer than a week [ 2 , 4 , 24 ]. Nonetheless, transmission has also been reported between cages in farm and farm to farm as well as from wild or escaped fish that play a role as a reservoir [ 2 ], a recent survey conducted in Austria showed that the bacterium was present in low numbers even in externally healthy wild fish populations [ 47 ]. Moreover, sea lice ( Lepeophteirus salmonis ) have been suspected to act as a vector; however, this has not been confirmed, even if treatment against sea lice is known to have a significant impact on the occurrence of BKD [ 4 , 20 ].…”
Section: Routes Of Infection and Risk Factors Of R Salmmentioning
confidence: 99%